Laminate, optical member and optical device

The laminate structure with a void layer and an adhesive layer, using a specific (meth)acrylic polymer and silane coupling agent, addresses the issue of adhesive penetration in optical devices, maintaining adhesive strength and refractive index stability.

JP2025054625APending Publication Date: 2025-04-08NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023163762
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The use of void layers in optical devices to replace air layers for total reflection can lead to issues such as adhesive penetration into the voids, reducing porosity and refractive index, especially under high temperature and humidity conditions.

Method used

A laminate structure comprising a void layer and an adhesive layer, where the adhesive layer is directly laminated on one or both sides of the void layer, and is formed using a (meth)acrylic polymer and a monomer-type silane coupling agent, with a limited content of monomeric silane coupling agent to prevent adhesive penetration.

Benefits of technology

The proposed laminate structure maintains high adhesive strength while preventing adhesive penetration into the void layer, thus preserving the porosity and refractive index of the void layer even under harsh environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054625000001_ABST
    Figure 2025054625000001_ABST
Patent Text Reader

Abstract

To provide a laminate which achieves both a pressure-sensitive adhesive force or an adhesive force and difficulty in permeation of a pressure-sensitive adhesive or an adhesive into a void of a void layer.SOLUTION: A laminate 10 comprises a void layer 11 and a pressure-sensitive adhesive layer 12, wherein the pressure-sensitive adhesive layer 12 is directly laminated on one surface or both surfaces of the void layer 11, the pressure-sensitive adhesive layer 12 is formed from a pressure-sensitive adhesive including a (meth)acrylic polymer and a monomer type silane coupling agent, the content of the monomer type silane coupling agent is 5.0 pts.mass or less based on 100 pts.mass of the (meth)acrylic polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate, an optical member, and an optical device. [Background technology]

[0002] In optical devices, for example, an air layer with a low refractive index is used as a total reflection layer. Specifically, for example, each optical film component (for example, a light guide plate and a reflector) in a liquid crystal device is laminated via an air layer. However, if each component is separated by an air layer, problems such as bending of the component may occur, especially when the component is large. In addition, due to the trend of making devices thinner, it is desired to integrate each component. For this reason, each component is integrated with a pressure-sensitive adhesive without an air layer (for example, Patent Document 1). However, if the air layer that plays the role of total reflection is lost, optical properties such as light leakage may be deteriorated.

[0003] Therefore, it has been proposed to use a low refractive index layer instead of the air layer. For example, Patent Document 2 describes a structure in which a layer having a lower refractive index than the light guide plate is inserted between the light guide plate and the reflector plate. As the low refractive index layer, for example, a gap layer having voids is used in order to make the refractive index as close as possible to that of air.

[0004] Furthermore, in order to introduce a void layer into a device, an integrated structure with a tacky adhesive layer has also been proposed (Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-156082 A [Patent Document 2] Japanese Patent Application Publication No. 10-62626 [Patent Document 3] JP 2014-46518 A Summary of the Invention [Problem to be solved by the invention]

[0006] The void layer is used by, for example, laminating it with another layer via a tacky adhesive layer. However, when the void layer and the tacky adhesive layer are laminated, the adhesive or the adhesive constituting the tacky adhesive layer penetrates into the voids of the void layer and fills the voids, which may reduce the porosity of the void layer and increase the refractive index. The higher the porosity of the void layer, the easier it is for the adhesive or the adhesive to penetrate. In addition, in a high temperature environment, the adhesive or the adhesive is more likely to penetrate into the voids due to molecular motion (reduction in elastic modulus) of the adhesive or the adhesive. In a high humidity environment, the adhesive or the adhesive is more likely to penetrate into the voids due to water absorption by the adhesive or the adhesive.

[0007] In order to suppress or prevent the pressure-sensitive adhesive or bonding agent from penetrating into the voids, the pressure-sensitive adhesive or bonding agent should have as high an elastic modulus (hardness) as possible. However, if the pressure-sensitive adhesive or bonding agent has a high elastic modulus (hardness), the adhesive strength or bonding strength may be reduced. Conversely, if the pressure-sensitive adhesive or bonding agent has a low elastic modulus (softness), it is easy to obtain high adhesive strength or bonding strength, but the pressure-sensitive adhesive or bonding agent may easily penetrate into the voids.

[0008] Therefore, an object of the present disclosure is to provide a laminate, an optical member, and an optical device that achieve both adhesive strength or bonding strength and resistance to penetration of an adhesive or bonding agent into the voids in the void layer. [Means for solving the problem]

[0009] In order to achieve the above object, the laminate of the present disclosure comprises: A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, the adhesive layer is formed of an adhesive containing a (meth)acrylic polymer and a monomer-type silane coupling agent, The content of the monomeric silane coupling agent is 5.0 parts by mass or less based on 100 parts by mass of the (meth)acrylic polymer.

[0010] The optical member of the present disclosure is characterized by including the laminate of the present disclosure.

[0011] The optical device according to the present disclosure is characterized by including the optical member according to the present disclosure. Effect of the Invention

[0012] According to the present disclosure, it is possible to provide a laminate, an optical member, and an optical device that achieve both adhesive strength or bonding strength and resistance to penetration of an adhesive or bonding agent into the voids in the void layer. [Brief description of the drawings]

[0013] [Figure 1] 1(a) and (b) are cross-sectional views illustrating examples of the configuration of a laminate according to the present disclosure. [Diagram 2] 2(a) and (b) are cross-sectional views showing another example of the configuration of the laminate of the present disclosure. [Diagram 3] 3(a) and (b) are cross-sectional views showing still another example of the configuration of the laminate of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Next, the present disclosure will be described in more detail with reference to examples. However, the present disclosure is not limited to the following description.

[0015] In the laminate of the present disclosure, the (meth)acrylic polymer may have a weight average molecular weight (Mw) of 1.5 million to 4 million, for example.

[0016] In the laminate of the present disclosure, for example, the adhesive layer may be formed from an adhesive containing the (meth)acrylic polymer and a crosslinking agent, and the adhesive may have a gel fraction of more than 85%.

[0017] In the laminate of the present disclosure, for example, the (meth)acrylic polymer may contain 1 to 30 mass % of a nitrogen-containing monomer as a monomer unit. In the present disclosure, unless otherwise specified, "mass %" and "weight %" may be read as interchangeable, and "parts by mass" and "parts by weight" may be read as interchangeable.

[0018] In the laminate of the present disclosure, for example, the nitrogen-containing monomer may be a heterocycle-containing acrylic monomer.

[0019] In the laminate of the present disclosure, for example, the (meth)acrylic polymer may contain 0.5 to 20 mass % of acrylic acid as a monomer unit.

[0020] In the laminate of the present disclosure, for example, the void layer may not contain an organic fluorine compound. By making the void layer free of an organic fluorine compound, it is possible to provide a laminate, an optical member, and an optical device that include an environmentally friendly void layer. Note that the void layer "does not contain" an organic fluorine compound means that an organic fluorine compound cannot be detected by analyzing the void layer, and the presence of an organic fluorine compound in the void layer cannot be proven.

[0021] In the laminate of the present disclosure, for example, the change in refractive index of the porous layer before and after a heat durability test in which the laminate is maintained at a temperature of 65° C. and a relative humidity of 95% for 500 hours may satisfy the following formula (1). |nn 0 |<0.04 (1) In the formula (1), n is the refractive index of the air gap layer after the heat durability test, n 0 is the refractive index of the air gap layer before the heat durability test.

[0022] In the laminate of the present disclosure, for example, an intermediate layer may be present between the void layer and the adhesive layer, and the intermediate layer may be a layer formed by combining the void layer and the adhesive layer.

[0023] In the laminate of the present disclosure, the intermediate layer may have a thickness of 10 to 100 nm, for example.

[0024] In the present disclosure, the "adhesive layer" refers to a layer formed by at least one of an adhesive and an adhesive. In the present disclosure, unless otherwise specified, the "adhesive layer" may be an "adhesive layer" formed by an adhesive, an "adhesive layer" formed by an adhesive, or a layer containing both an adhesive and an adhesive. In the present disclosure, an adhesive and an adhesive may be collectively referred to as an "adhesive". In general, an agent having a relatively weak adhesive or bonding strength (e.g., an agent that allows the adherend to be peeled off again) may be called an "adhesive", and an agent having a relatively strong adhesive or bonding strength (e.g., an agent that does not allow the adherend to be peeled off again or is very difficult to peel off again) may be called an "adhesive". In the present disclosure, there is no clear distinction between an adhesive and an adhesive. In the present disclosure, there is no clear distinction between "adhesive strength" and "adhesive strength".

[0025] In addition, in the present disclosure, "on" or "on the surface" may mean a state of being in direct contact with the surface or a state of being via another layer or the like.

[0026] In the laminate of the present disclosure, for example, the (meth)acrylic polymer may be a (meth)acrylic polymer having a weight average molecular weight of 2,000,000 to 3,500,000 obtained by polymerizing, as monomer components, 3 to 20 mass% of a heterocycle-containing acrylic monomer (heterocycle-containing acrylate), 0.5 to 5 mass% of (meth)acrylic acid, 0.05 to 2 mass% of a hydroxyalkyl (meth)acrylate, and 83 to 96.45 mass% of an alkyl (meth)acrylate.

[0027] In the laminate of the present disclosure, for example, in the adhesive layer, the nitrogen-containing monomer may be a monomer having one or two reactive double bonds in one molecule. The monomer having one or two reactive double bonds in one molecule may be, for example, a heterocycle-containing acrylic monomer (heterocycle-containing acrylate).

[0028] In the laminate of the present disclosure, the gel fraction of the adhesive forming the adhesive layer may be, for example, 85 mass % or more, or may exceed 85 mass %, for example, 90 mass % or more, 91 mass % or more, or 93 mass % or more, and may be, for example, 100 mass % or less, 99 mass % or less, or 98 mass % or less.

[0029] In the laminate of the present disclosure, the initial refractive index of the porous layer before the heat durability test (hereinafter sometimes referred to as "initial refractive index") may be, for example, 1.30 or less or less than 1.30, and may be, for example, 1.25 or less, less than 1.25, 1.20 or less, or less than 1.20. The lower limit of the initial refractive index may be, for example, 1.05 or more, 1.06 or more, 1.07 or more, or 1.08 or more.

[0030] In the laminate of the present disclosure, the refractive index of the void layer after the heat durability test may be, for example, 1.50 or less or less than 1.50, and may be, for example, 1.40 or less, less than 1.40, 1.30 or less, or less than 1.30. The lower limit of the refractive index of the void layer after the heat durability test may be, for example, 1.05 or more, 1.06 or more, 1.07 or more, or 1.08 or more.

[0031] In the laminate of the present disclosure, the |nn 0 The change in the refractive index of the air gap layer, represented by |nn, may be, for example, less than 0.04 as shown in the above formula (1). 0 The change in refractive index of the air gap layer, represented by |nn, may be, for example, 0.03 or less, less than 0.03, 0.02 or less, or less than 0.02. 0 The lower limit of the change in the refractive index of the air gap layer represented by | is not particularly limited, but may be, for example, 0 or more, or may be a value exceeding 0.

[0032] In the laminate of the present disclosure, before and after a heat durability test in which the laminate is held at a temperature of 65° C. and a relative humidity of 95% for 500 hours, (|nn 0 | / n 0 The increase rate (%) of the refractive index of the porous layer, expressed as (|nn 0 | / n 0 The increase rate of the refractive index of the porous layer, represented by (|nn)×100, may be, for example, 2.0% or less, less than 2.0%, 1.0% or less, or less than 1.0%. 0 | / n 0 The lower limit of the increase rate of the refractive index of the air gap layer, expressed by n ) × 100, is not particularly limited, but may be, for example, 0 or more, or may be a value exceeding 0. 0 is the refractive index (initial refractive index) of the air gap layer before the heat durability test, as in the above formula (1), and n is the refractive index of the air gap layer after the heat durability test, as in the above formula (1).

[0033] In the laminate of the present disclosure, for example, the porosity of the porous layer may be 35 volume % or more.

[0034] In the laminate of the present disclosure, for example, the porous layer may be a porous body in which microporous particles are chemically bonded to each other.

[0035] In the laminate of the present disclosure, the adhesive layer may be a layer formed by a method including, for example, a step of preparing an adhesive coating liquid containing a (meth)acrylic polymer and a monomer-type silane coupling agent, a step of applying the adhesive coating liquid to a substrate, and a step of drying the substrate coated with the adhesive coating liquid by heating. In the laminate of the present disclosure, for example, the adhesive layer may be formed from an adhesive coating liquid having a specific composition and integrated with the void layer. This can suppress significant penetration of the adhesive layer into the void layer, especially under a long-term heat durability test. The adhesive coating liquid may further include, for example, a crosslinking agent, or may include other components as described below.

[0036] In the laminate of the present disclosure, the reason (mechanism) for achieving both the adhesive force or bonding force and the difficulty of the adhesive or adhesive penetrating into the voids is, for example, considered to be as follows. For example, by forming an adhesive layer using a specific adhesive, it is possible to achieve both the adhesive force or bonding force and the difficulty of the adhesive or adhesive penetrating into the voids. More specifically, for example, by forming an adhesive layer using the above-mentioned specific (meth)acrylic polymer and, if necessary, a crosslinking agent, an intermediate layer is formed by merging a part of the void layer with a part of the adhesive layer. And, by using the above-mentioned specific (meth)acrylic polymer, the intermediate layer does not spread excessively even under conditions such as the heat durability test. In addition, the intermediate layer acts as a stopper, and the reduction in porosity caused by the voids in the void layer being filled with the adhesive can be suppressed. Even if the molecular motion of the adhesive increases under heating, if the elastic modulus of the adhesive is high, the intermediate layer formed from the adhesive and the high void layer is likely to become a strong and dense stopper, and the penetration of the adhesive into the high void layer is suppressed. However, these mechanisms are merely examples and do not limit the present disclosure in any way.

[0037] In addition, the adhesive coating liquid may contain a monomer having one or two reactive double bonds in one molecule, and may undergo a crosslinking reaction with a crosslinking agent such as an isocyanate crosslinking agent or an epoxy crosslinking agent when heated. During the crosslinking reaction, the monomer having one or two reactive double bonds in one molecule and the organic peroxide, which is a hydrogen abstraction initiator, coexist, and it is believed that the semi-high molecular weight polymer component having a molecular weight of 10,000 or less contained in the adhesive coating liquid is crosslinked at a high density, and the penetration of the component from the adhesive coating liquid into the void layer can be suppressed to a higher level. That is, the semi-high molecular weight polymer component having a molecular weight of 10,000 or less is easily penetrated into the voids of the void layer due to its small molecular size, but the crosslinking reaction increases the molecular size, and therefore the penetration into the voids of the void layer is suppressed. Furthermore, it is presumed that the coexistence of a monomer having one or two reactive double bonds in one molecule during the crosslinking reaction enables a graft reaction with the (meth)acrylic polymer main chain and high-density crosslinking starting from the graft chain, thereby reducing the amount of semi-high molecular weight polymer that can become a sol component. However, these mechanisms are also examples and do not limit the present disclosure in any way.

[0038] In the adhesive coating liquid for forming the adhesive layer in the laminate of the present disclosure, the nitrogen-containing monomer preferably has a small number of functional groups (the number of reactive double bonds in one molecule) in order to efficiently crosslink main chains in a graft reaction. For example, as described above, the number of reactive double bonds in one molecule is preferably one or two.

[0039] In addition, even if a monomer having one or two reactive double bonds is mixed during the production of a (meth)acrylic polymer, it is difficult to reduce the amount of the semi-high molecular weight polymer (which has a small molecular weight and is easily permeated into the voids of the void layer) as described above. However, according to the present disclosure, by using a pressure-sensitive adhesive coating liquid in which a monomer having one or two reactive double bonds is mixed into a (meth)acrylic polymer later and then crosslinking the adhesive, for example, a graft reaction as described above occurs, and the amount of the semi-high molecular weight polymer can be reduced.

[0040] In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic. For example, "(meth)acrylic acid" means at least one of acrylic acid and methacrylic acid. "(meth)acrylic acid ester" means at least one of acrylic acid ester and methacrylic acid ester. "(meth)acrylate" means at least one of methyl acrylate and methyl methacrylate.

[0041] In the present disclosure, the term "(meth)acrylic polymer" refers to a polymer having a structure obtained by polymerizing a component containing at least one selected from the group consisting of acrylic acid, methacrylic acid, acrylic acid esters, methacrylic acid esters, monomers having an acryloyl group, and monomers having a methacryloyl group. The component may or may not contain a substance other than at least one selected from the group consisting of acrylic acid, methacrylic acid, acrylic acid esters, methacrylic acid esters, monomers having an acryloyl group, and monomers having a methacryloyl group.

[0042] In the present disclosure, the term "acrylic monomer" refers to, for example, a monomer including at least one selected from the group consisting of acrylic acid, an acrylic ester, and a monomer having an acryloyl group.

[0043] In the present disclosure, the term "isocyanate-based crosslinking agent" refers to, for example, a crosslinking agent having an isocyanate group (isocyanato group) in the molecule. In the present disclosure, the number of isocyanate groups (isocyanato groups) in one molecule of the isocyanate-based crosslinking agent is not particularly limited, but is preferably 2 or more, and may be, for example, 2, 3, or 4, and the upper limit is not particularly limited, but is, for example, 10 or less.

[0044] In the present disclosure, the term "epoxy crosslinking agent" refers to, for example, a crosslinking agent having an epoxy group in the molecule. In the present disclosure, the number of epoxy groups in one molecule of the epoxy crosslinking agent is not particularly limited, but is preferably 2 or more, and may be, for example, 2, 3, or 4, and the upper limit is not particularly limited, but is, for example, 10 or less.

[0045] [1. Laminate, optical member, and optical device] As described above, the laminate of the present disclosure includes a void layer and a tacky adhesive layer, and the tacky adhesive layer is directly laminated on one or both sides of the void layer. In the present disclosure, the tacky adhesive layer is "directly laminated" on the void layer, for example, the tacky adhesive layer may be in direct contact with the void layer, or the tacky adhesive layer may be laminated on the void layer via the intermediate layer.

[0046] The cross-sectional view of Fig. 1(a) shows an example of the configuration of the laminate of the present disclosure. As shown in the figure, in this laminate 10, a tacky adhesive layer 12 is directly laminated on one side of a void layer 11. In addition, the cross-sectional view of Fig. 1(b) shows another example of the configuration of the laminate of the present disclosure. As shown in the figure, in this laminate 10a, a tacky adhesive layer 12 is directly laminated on both sides of a void layer 11.

[0047] In addition, as described above, the laminate of the present disclosure may have an intermediate layer between the void layer and the tacky adhesive layer, and the intermediate layer may be a layer formed by merging the void layer and the tacky adhesive layer. FIG. 2 shows an example of such a laminate of the present disclosure. As shown in the figure, the laminate 10b of FIG. 2(a) has a tacky adhesive layer 12 directly laminated on one side of the void layer 11. This laminate 10b is the same as the laminate 10 of FIG. 1(a) except that an intermediate layer 13 is present between the void layer 11 and the tacky adhesive layer 12. The intermediate layer 13 is a layer formed by merging the void layer 11 and the tacky adhesive layer 12. As shown in the figure, the laminate 10c of FIG. 2(b) has a tacky adhesive layer 12 directly laminated on both sides of the void layer 11. This laminate 10c is the same as the laminate 10a of FIG. 1(b) except that an intermediate layer 13 is present between the void layer 11 and each tacky adhesive layer 12. The intermediate layer 13 is a layer formed by combining the void layer 11 and the adhesive layer 12, as in FIG. 2(a).

[0048] The laminate of the present disclosure may or may not include other components other than the void layer, the tacky adhesive layer, and the intermediate layer. The other components are not particularly limited, and may be, for example, a substrate. The substrate is also not particularly limited, and may be, for example, a film (for example, a resin film), a glass plate, or the like, as described below. FIG. 3 shows an example of such a laminate of the present disclosure. The laminate 10d of FIG. 3(a) is the same as the laminate 10b of FIG. 2(a) except that, as shown in the figure, a substrate 14 is provided in direct contact with the surface of the void layer 11 opposite the tacky adhesive layer 12, and on the surface of the tacky adhesive layer 12 opposite the void layer 11. The laminate 10e of FIG. 3(b) is the same as the laminate 10c of FIG. 2(b) except that, as shown in the figure, a substrate 14 is provided in direct contact with the surface of the tacky adhesive layer 12 on both sides opposite the void layer 11. In FIG. 3(a) and FIG. 3(b), a substrate 14 is provided on both sides of the laminate. However, the present disclosure is not limited thereto, and for example, the substrate 14 may be provided on only one side. In addition, in FIG. 3(a) and FIG. 3(b), the substrate 14 is provided so as to be in direct contact with the void layer 11 or the tacky adhesive layer 12. However, the present disclosure is not limited thereto, and for example, other components may be present between the substrate 14 and the void layer 11 or the tacky adhesive layer 12. The other components are not particularly limited, and may be, for example, an optical functional layer. The optical functional layer is also not particularly limited, and may be, for example, an optical functional layer used in a general optical film, and may be, for example, a microlens film, a prism film, a diffusion film, a polarizing reflection film, a polarizing film, a retardation film, a high refractive index layer, etc.

[0049] The laminate of the present disclosure may have a light transmittance of 80% or more for the laminate of the adhesive layer and the void layer, or the laminate of the adhesive layer, the intermediate layer and the void layer. The laminate may have a haze of 3% or less for example. The light transmittance may be, for example, 82% or more, 84% or more, 86% or more, or 88% or more, and the upper limit is not particularly limited, but is ideally 100%, and may be, for example, 95% or less, 92% or less, 91% or less, or 90% or less. The haze of the laminate may be measured, for example, by the same method as the haze of the void layer described later. The light transmittance is the transmittance of light with a wavelength of 550 nm, and may be measured, for example, by the following measurement method.

[0050] (Method of measuring light transmittance) The laminate is treated as a sample to be measured using a spectrophotometer U-4100 (trade name of Hitachi, Ltd.). The total light transmittance (light transmittance) of the sample is measured when the total light transmittance of air is taken as 100%. The total light transmittance (light transmittance) value is taken as the value measured at a wavelength of 550 nm.

[0051] In the laminate of the present disclosure, for example, the adhesive strength or adhesion of the tacky adhesive layer may be, for example, 0.7N / 25mm or more, 0.8N / 25mm or more, 1.0N / 25mm or more, or 1.5N / 25mm or more, and may be 50N / 25mm or less, 30N / 25mm or less, 10N / 25mm or less, 5N / 25mm or less, or 3N / 25mm or less. From the viewpoint of the risk of peeling during handling when the laminate is attached to another layer, it is preferable that the adhesive strength or adhesion of the tacky adhesive layer is not too low. In addition, from the viewpoint of rework when reattaching, it is preferable that the adhesive strength or adhesion of the tacky adhesive layer is not too high. The adhesive strength or adhesion of the tacky adhesive layer can be measured, for example, as follows.

[0052] (Method of measuring adhesive strength or adhesion) The laminated film of the present disclosure (a laminated body of the present disclosure formed on a resin film substrate) is sampled in a rectangular shape of 50 mm x 140 mm, and the sample is fixed to a stainless steel plate with double-sided tape. An acrylic adhesive layer (thickness 20 μm) is attached to a PET film (T100: manufactured by Mitsubishi Plastics Film Co., Ltd.), and an adhesive tape piece cut to 25 mm x 100 mm is attached to the opposite side of the laminated film of the present disclosure to the resin film, and laminated with the PET film. Next, the sample is chucked in an autograph tensile tester (manufactured by Shimadzu Corporation: AG-Xplus) so that the chuck distance is 100 mm, and then a tensile test is performed at a tensile speed of 0.3 m / min. The average test force obtained by performing a 50 mm peel test is the adhesive peel strength, i.e., the adhesive force. The adhesive force can also be measured by the same measurement method. In the present disclosure, there is no clear distinction between "adhesive strength" and "adhesive strength".

[0053] The laminate of the present disclosure may be formed on a substrate such as a film. The film may be, for example, a resin film. In general, a relatively thin one may be called a "film" and a relatively thick one may be called a "sheet", but in the present disclosure, there is no particular distinction between the "film" and the "sheet".

[0054] The substrate is not particularly limited, and for example, a substrate made of a thermoplastic resin, a substrate made of glass, an inorganic substrate such as silicon, a plastic molded from a thermosetting resin, an element such as a semiconductor, a carbon fiber material such as a carbon nanotube, etc. can be preferably used, but is not limited thereto. The form of the substrate can be, for example, a film, a plate, etc. Examples of the thermoplastic resin include polyethylene terephthalate (PET), acrylic, cellulose acetate propionate (CAP), cycloolefin polymer (COP), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), etc.

[0055] The optical member of the present disclosure is not particularly limited, and may be, for example, an optical film including the laminate of the present disclosure.

[0056] The optical apparatus (optical device) of the present disclosure is not particularly limited, and may be, for example, an image display apparatus or a lighting apparatus. Examples of the image display apparatus include a liquid crystal display, an organic EL (Electro Luminescence) display, and a micro LED (Light Emitting Diode) display. Examples of the lighting apparatus include an organic EL light.

[0057] [2.Void layer] Hereinafter, the void layer in the laminate of the present disclosure (hereinafter, sometimes referred to as the "void layer of the present disclosure") will be described with examples. However, the void layer of the present disclosure is not limited thereto.

[0058] The porous layer of the present disclosure may have a porosity of 35 volume % or more and a peak pore size of 50 nm or less, for example, although this is merely an example and the porous layer of the present disclosure is not limited thereto.

[0059] The porosity may be, for example, 35% by volume or more, 38% by volume or more, or 40% by volume or more, and may be 90% by volume or less, 80% by volume or less, or 75% by volume or less. The porous layer of the present disclosure may be, for example, a highly porous layer having a porosity of 60% by volume or more.

[0060] The porosity can be measured, for example, by the following measurement method.

[0061] (Method of measuring void ratio) If the layer to be measured for porosity is a single layer containing voids, the ratio (volume ratio) of the constituent material of the layer to air can be calculated by a standard method (e.g., measuring the weight and volume to calculate the density), and the porosity (volume %) can be calculated from this. In addition, since there is a correlation between the refractive index and the porosity, it is also possible to calculate the porosity from the refractive index value of the layer, for example. Specifically, the porosity is calculated from the refractive index value measured by an ellipsometer using the Lorentz-Lorenz's formula.

[0062] The porous layer of the present disclosure can be produced, for example, by chemically bonding pulverized gel (microporous particles) as described below. In this case, for convenience, the pores in the porous layer can be divided into the following three types (1) to (3). (1) Voids in the raw gel itself (within the particles) (2) Voids in the gel pulverized material units (3) Gaps between the gel particles caused by accumulation of the gel particles

[0063] The voids (2) are voids formed during pulverization in addition to the voids (1) that may be formed in each block when each particle group produced by pulverizing the gel is considered as one block, regardless of the size, dimensions, etc. of the pulverized gel (microporous particles). The voids (3) are voids that are generated during pulverization (e.g., media-less pulverization, etc.) because the size, dimensions, etc. of the pulverized gel (microporous particles) become uneven. The porous layer of the present disclosure has, for example, the voids (1) to (3) described above, and thus has an appropriate porosity and peak pore size.

[0064] The peak pore diameter may be, for example, 5 nm or more, 10 nm or more, or 20 nm or more, or 50 nm or less, 40 nm or less, or 30 nm or less. In the porous layer, if the peak pore diameter is too large when the porosity is high, the light is scattered and the layer becomes opaque. In the present disclosure, the lower limit of the peak pore diameter of the porous layer is not particularly limited, but if the peak pore diameter is too small, it is difficult to increase the porosity, so it is preferable that the peak pore diameter is not too small. In the present disclosure, the peak pore diameter can be measured, for example, by the following method.

[0065] (Method of measuring peak pore diameter) A pore distribution / specific surface area measuring device (BELLSORP MINI / product name of Microtrack Bell Co., Ltd.) is used to calculate the peak pore diameter from the results of calculating the BJH plot and BET plot by nitrogen adsorption and the isothermal adsorption curve.

[0066] Furthermore, the thickness of the air gap layer of the present disclosure is not particularly limited, and may be, for example, 100 nm or more, 200 nm or more, or 300 nm or more, and may be 10,000 nm or less, 5,000 nm or less, or 2,000 nm or less.

[0067] In the void layer of the present disclosure, for example, as described below, by using a pulverized product of the porous gel, the three-dimensional structure of the porous gel is destroyed, and a new three-dimensional structure different from the porous gel is formed. In this way, the void layer of the present disclosure is a layer in which a new pore structure (new void structure) that cannot be obtained in a layer formed from the porous gel is formed, and a nanoscale void layer with high porosity can be formed. In addition, in the void layer of the present disclosure, for example, when the void layer is a silicone porous body, for example, the number of siloxane bond functional groups of the silicon compound gel is adjusted, and the pulverized products are chemically bonded to each other. Here, the "silicone porous body" refers to a polymeric porous body containing a siloxane bond, and includes, for example, a porous body containing silsesquioxane as a constituent unit. In addition, since a new three-dimensional structure is formed as a precursor of the void layer, and then chemically bonded (e.g., cross-linked) in a bonding step, the void layer of the present disclosure, for example, when the void layer is a functional porous body, has a structure with voids, but can maintain sufficient strength and flexibility. Therefore, according to the present disclosure, the void layer can be easily and simply applied to various objects.

[0068] The void layer of the present disclosure contains, for example, pulverized porous gel, and the pulverized materials are chemically bonded to each other, as described below. In the void layer of the present disclosure, the form of chemical bonding (chemical bonding) between the pulverized materials is not particularly limited, and specific examples of the chemical bonding include cross-linking. The method of chemically bonding the pulverized materials to each other is, for example, as described in detail in the manufacturing method of the void layer described above.

[0069] The crosslinked bond is, for example, a siloxane bond. Examples of the siloxane bond include the following T2 bond, T3 bond, and T4 bond. When the silicone porous body of the present disclosure has a siloxane bond, it may have, for example, any one type of bond, any two types of bonds, or all three types of bonds. The higher the ratio of T2 and T3 among the siloxane bonds, the more flexible the gel is, and the gel's original properties can be expected, but the film strength becomes weak. On the other hand, when the ratio of T4 among the siloxane bonds is high, the film strength is easily expressed, but the void size becomes small and the flexibility becomes weak. For this reason, it is preferable to change the ratio of T2, T3, and T4 depending on the application, for example.

[0070] [ka]

[0071] When the porous layer of the present disclosure has the siloxane bond, the ratio of T2, T3 and T4, for example, when expressed relatively with T2 being "1", is T2:T3:T4=1:[1-100]:[0-50], 1:[1-80]:[1-40], 1:[5-60]:[1-30].

[0072] In addition, in the porous layer of the present disclosure, for example, the silicon atoms contained therein are preferably siloxane-bonded.Specifically, the ratio of unbonded silicon atoms (i.e., residual silanol) to all silicon atoms contained in the silicone porous body is, for example, less than 50%, 30% or less, or 15% or less.

[0073] In addition, as described above, the void layer of the present disclosure may be, for example, substantially free of a fluorine compound. By making the void layer substantially free of a fluorine compound, for example, the penetration of a pressure-sensitive adhesive or adhesive into the voids of the void layer is further suppressed, and as a result, the increase in the refractive index after the heat durability test is further suppressed.

[0074] The void layer of the present disclosure has, for example, a pore structure. In the present disclosure, the void size of the pores refers to the diameter of the long axis of the void (hole) among the diameter of the long axis and the diameter of the short axis. The pore size is, for example, 5 nm to 50 nm. The lower limit of the void size is, for example, 5 nm or more, 10 nm or more, or 20 nm or more, and the upper limit is, for example, 50 nm or less, 40 nm or less, or 30 nm or less, and the range is, for example, 5 nm to 50 nm, or 10 nm to 40 nm. The preferred void size is determined depending on the application of the void structure, so it is necessary to adjust the void size to a desired void size depending on the purpose, for example. The void size can be evaluated, for example, by the following method.

[0075] (Cross-sectional SEM observation of void layer) In the present disclosure, the morphology of the void layer can be observed and analyzed using a SEM (scanning electron microscope). Specifically, for example, the void layer is subjected to FIB processing (accelerating voltage: 30 kV) under cooling, and a cross-sectional electron image can be obtained at a magnification of 100,000 times using a FIB-SEM (manufactured by FEI: product name Helios NanoLab600, accelerating voltage: 1 kV) for the obtained cross-sectional sample.

[0076] (Evaluation of void size) In the present disclosure, the pore size can be quantified by the BET test method. Specifically, 0.1 g of a sample (porous layer of the present disclosure) is placed in the capillary of a pore distribution / specific surface area measuring device (BELLSORP MINI / product name of Microtrack Bell Co., Ltd.), and then dried under reduced pressure at room temperature for 24 hours to remove the gas from the pore structure. Then, nitrogen gas is adsorbed onto the sample, and a BET plot, a BJH plot, and an adsorption isotherm are plotted to determine the pore distribution. This allows the pore size to be evaluated.

[0077] The void layer of the present disclosure may have a pore structure (porous structure) as described above, and may be, for example, an open-cell structure in which the pore structure is continuous. The open-cell structure means, for example, that the pore structure is three-dimensionally connected in the void layer, and can also be said to be a state in which the internal voids of the pore structure are continuous. When the porous body has an open-cell structure, it is possible to increase the porosity in the bulk, but when closed-cell particles such as hollow silica are used, an open-cell structure cannot be formed. In contrast, the void layer of the present disclosure has a three-dimensional dendritic structure in which the dendritic particles settle and deposit in the coating film (coating film of the sol containing the pulverized porous gel), and therefore the open-cell structure can be easily formed. In addition, it is more preferable that the void layer of the present disclosure forms a monolith structure in which the open-cell structure has a plurality of pore distributions. The monolith structure refers to, for example, a structure in which fine nano-sized voids exist, and a hierarchical structure in which the nano-voids are aggregated and exist as an open-cell structure. When forming the monolith structure, for example, it is possible to achieve both film strength and high porosity by imparting film strength with fine voids and high porosity with coarse open-cell voids. To form such a monolith structure, for example, it is important to first control the pore distribution of the void structure to be generated in the porous gel prior to pulverization into the pulverized material. In addition, for example, when pulverizing the porous gel, the particle size distribution of the pulverized material can be controlled to a desired size to form the monolith structure.

[0078] In the air gap layer of the present disclosure, the haze indicating transparency is not particularly limited, and the lower limit is, for example, 0.1% or more, 0.2% or more, or 0.3% or more, and the upper limit is, for example, 10% or less, 5% or less, or 3% or less, and the range is, for example, 0.1 to 10%, 0.2 to 5%, or 0.3 to 3%.

[0079] The haze can be measured, for example, by the following method.

[0080] (Hayes's rating) The porous layer (porous layer of the present disclosure) is cut to a size of 50 mm x 50 mm, and is set in a haze meter (HM-150 manufactured by Murakami Color Research Laboratory Co., Ltd.) to measure the haze. The haze value is calculated according to the following formula. Haze (%) = [Diffuse transmittance (%) / Total light transmittance (%)] x 100 (%)

[0081] The refractive index is generally the ratio of the transmission speed of the wavefront of light in vacuum to the propagation speed in the medium, and is called the refractive index of the medium.The refractive index of the air gap layer of the present disclosure is not particularly limited, and its upper limit is, for example, 1.3 or less, less than 1.3, 1.25 or less, 1.2 or less, 1.15 or less, its lower limit is, for example, 1.05 or more, 1.06 or more, 1.07 or more, and its range is, for example, 1.05 or more and 1.3 or less, 1.05 or more and 1.3 or less, 1.05 or more and 1.25 or less, 1.06 or more and 1.2 or less, 1.07 or more and 1.15 or less.

[0082] In the present disclosure, the refractive index refers to a refractive index measured at a wavelength of 550 nm unless otherwise specified. The method for measuring the refractive index is not particularly limited, and can be measured, for example, by the following method.

[0083] (Refractive index evaluation) A laminate sample is prepared by laminating an adhesive onto the void layer. A prism of a prism coupler (manufactured by Meritricon) is attached to the substrate side of the sample, and the total reflection critical angle is measured using a laser. The refractive index is calculated from the critical angle.

[0084] The thickness of the porous layer of the present disclosure is not particularly limited, and the lower limit is, for example, 0.05 μm or more, 0.1 μm or more, and the upper limit is, for example, 1000 μm or less, 100 μm or less, and the range is, for example, 0.05 to 1000 μm, 0.1 to 100 μm.

[0085] The form of the porous layer of the present disclosure is not particularly limited, and may be, for example, a film shape or a block shape.

[0086] The method for producing the void layer of the present disclosure is not particularly limited, but can be produced by, for example, the methods described in WO 2019 / 065999 and WO 2019 / 065803. The descriptions in these publications are incorporated herein by reference.

[0087] [3. Adhesive coating fluid] In the laminate of the present disclosure, the adhesive layer can be formed, for example, using an adhesive coating liquid, as described above. In the present disclosure, the "adhesive" and the "adhesive" are not necessarily clearly distinguishable, as described later. In the present disclosure, the term "adhesive" includes both the "adhesive" and the "adhesive" unless otherwise specified. The adhesive coating liquid may be, for example, an adhesive coating liquid containing the (meth)acrylic polymer, or may be, for example, an adhesive coating liquid containing the monomer-type silane coupling agent, or may be, for example, an adhesive coating liquid further containing a crosslinking agent (e.g., an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent), or may further contain, for example, a monomer having one or two reactive double bonds in one molecule and an organic peroxide. The adhesive coating liquid is not particularly limited, but is, for example, as shown below.

[0088] The pressure-sensitive adhesive coating liquid may be, for example, a (meth)acrylic polymer containing, as monomer components, 3 to 20 mass % of a heterocycle-containing acrylic monomer, a (meth)acrylic polymer having a polymerizable functional group, 0.5 to 5 mass % of (meth)acrylic acid, 0.05 to 2 mass % of a hydroxyalkyl (meth)acrylate, and 83 to 96.45 mass % of an alkyl (meth)acrylate, and this (meth)acrylic polymer may be used as a base polymer.

[0089] As the heterocycle-containing acrylic monomer, for example, one having a polymerizable functional group and a heterocycle can be used without any particular limitation. Examples of the polymerizable functional group include a (meth)acryloyl group and a vinyl ether group. Among these, a (meth)acryloyl group is preferred. Examples of the heterocycle include a morpholine ring, a piperidine ring, a pyrrolidine ring, and a piperazine ring. Examples of the heterocycle-containing acrylic monomer include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine. Among these, N-acryloylmorpholine is preferred. The heterocycle-containing acrylic monomer can improve both the durability of heat resistance and moisture resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned. In the following, N-acryloylmorpholine may be referred to as "ACMO".

[0090] In addition, the heterocycle-containing acrylic monomer is preferable in that it can improve the adhesive strength of the pressure-sensitive adhesive layer (adhesive layer) to the optical film. In particular, it is preferable in that it can improve the adhesive strength to cyclic polyolefins such as norbornene-based resins, and is suitable when cyclic polyolefins are used as the optical film.

[0091] The heterocycle-containing acrylic monomer is used in an amount of, for example, 3 to 20% by mass based on the total amount of monomer components forming the (meth)acrylic polymer. The amount of the heterocycle-containing acrylic monomer may be, for example, 4 to 19% by mass or 6 to 18% by mass. The amount of the heterocycle-containing acrylic monomer is preferably not less than the above range from the viewpoint of heat resistance and moisture resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned. The amount of the heterocycle-containing acrylic monomer is preferably not more than the above range from the viewpoint of moisture resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned. The amount of the heterocycle-containing acrylic monomer is preferably not more than the above range from the viewpoint of improving the adhesion of the pressure-sensitive adhesive layer (adhesive layer). The amount of the heterocycle-containing acrylic monomer is preferably not more than the above range from the viewpoint of adhesive strength.

[0092] As the (meth)acrylic acid, acrylic acid is particularly preferred.

[0093] (Meth)acrylic acid is used, for example, at a ratio of 0.5 to 20% by mass relative to the total amount of monomer components forming the (meth)acrylic polymer. The ratio of (meth)acrylic acid may be, for example, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, or 3% by mass or more, and may be, for example, 20% by mass or less, 15% by mass or less, 13% by mass or less, or 10% by mass or less. The ratio of (meth)acrylic acid is preferably not less than the above range from the viewpoint of heat resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned. In addition, the ratio of (meth)acrylic acid is preferably not more than the above range from the viewpoint of heat resistance and moisture resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned. In addition, the ratio of (meth)acrylic acid is preferably not more than the above range from the viewpoint of adhesive strength.

[0094] As the hydroxyalkyl (meth)acrylate, for example, those having a polymerizable functional group and a hydroxyl group can be used without any particular limitation.As the hydroxyalkyl (meth)acrylate, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, etc. are suitable.

[0095] The hydroxyalkyl (meth)acrylate is used, for example, at a ratio of 0.05 to 2 mass% based on the total amount of monomer components forming the (meth)acrylic polymer. The ratio of the hydroxyalkyl (meth)acrylate may be, for example, 0.075 to 1.5 mass% or 0.1 to 1 mass%. From the viewpoint of heat resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned, the ratio of the hydroxyalkyl (meth)acrylate is preferably not less than the above range. Also, from the viewpoint of heat resistance and moisture resistance when the pressure-sensitive adhesive layer is thinned, the ratio of the hydroxyalkyl (meth)acrylate is preferably not more than the above range. Also, from the viewpoint of adhesive strength, the ratio of the hydroxyalkyl (meth)acrylate is preferably not more than the above range.

[0096] The alkyl (meth)acrylate may have, for example, an average carbon number of the alkyl group of the alkyl (meth)acrylate of about 1 to 12. Incidentally, the (meth)acrylate refers to an acrylate and / or a methacrylate, and (meth) in the present disclosure has the same meaning. Specific examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, etc., which can be used alone or in combination. Among these, alkyl (meth)acrylates having an alkyl group with 1 to 9 carbon atoms are preferred.

[0097] The alkyl (meth)acrylate is used in an amount of, for example, 83 to 96.45% by mass based on the total amount of monomer components forming the (meth)acrylic polymer. The alkyl (meth)acrylate is usually the remainder other than the heterocycle-containing acrylic monomer, (meth)acrylic acid, and hydroxyalkyl (meth)acrylate.

[0098] As the monomer components forming the (meth)acrylic polymer, for example, in addition to the above-mentioned monomers, any other monomers can be used in an amount of 10% or less of the total amount of monomers, as long as the object of the present disclosure is not impaired.

[0099] Examples of the optional monomer include acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide propanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; and phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate. Examples of the nitrogen-containing vinyl monomer include maleimide, N-cyclohexylmaleimide, and N-phenylmaleimide; (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide (N-substituted) amide monomers; aminoethyl(meth)acrylate, aminopropyl(meth)acrylate, and (meth) Examples of such monomers include alkylaminoalkyl (meth)acrylate monomers such as N,N-dimethylaminoethyl acrylate, t-butylaminoethyl (meth)acrylate, and 3-(3-pyridyl)propyl (meth)acrylate; alkoxyalkyl (meth)acrylate monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; and succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide.

[0100] Furthermore, vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; and acrylic ester monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and 2-methoxyethyl acrylate can also be used.

[0101] Further, as copolymerizable monomers other than the above, there may be mentioned silane-based monomers containing silicon atoms, etc. Examples of the silane-based monomers include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, 10-acryloyloxydecyltriethoxysilane, etc.

[0102] As described above, the (meth)acrylic polymer used in the adhesive layer in the laminate of the present disclosure may have a weight average molecular weight (Mw) of, for example, 1.5 million to 4 million. The weight average molecular weight may be, for example, 1.8 million to 3.8 million, for example, 2 million to 3.5 million or 2.2 million to 3.3 million. The weight average molecular weight is preferably not smaller than the above range from the viewpoint of heat resistance and moisture resistance when the adhesive layer (adhesive layer) is thinned. In addition, the weight average molecular weight is preferably not larger than the above range from the viewpoint of durability, lamination property, and adhesive strength when the adhesive layer is thinned. In the present disclosure, the weight average molecular weight refers to a value measured by, for example, GPC (gel permeation chromatography) and calculated in terms of polystyrene.

[0103] The method for producing such a (meth)acrylic polymer is not particularly limited, and can be appropriately selected from known production methods such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymer may be any of a random copolymer, a block copolymer, a graft copolymer, etc.

[0104] In the solution polymerization, for example, ethyl acetate, toluene, etc. are used as a polymerization solvent. In a specific example of the solution polymerization, the reaction is carried out under a stream of an inert gas such as nitrogen, with the addition of a polymerization initiator, at a temperature of about 50 to 70° C., for about 1 to 30 hours.

[0105] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the radical polymerization are not particularly limited and can be appropriately selected and used. The weight average molecular weight of the (meth)acrylic polymer can be controlled by the amount of the polymerization initiator and chain transfer agent used and the reaction conditions, and the amount used is appropriately adjusted depending on the type of these.

[0106] Examples of the polymerization initiator include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate; di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butyl ... Examples of the initiator include, but are not limited to, peroxide initiators such as dicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butyl hydroperoxide, and hydrogen peroxide; and redox initiators combining a peroxide and a reducing agent, such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate.

[0107] The polymerization initiator may be used alone or in combination of two or more kinds. The total content of the polymerization initiator may be, for example, about 0.005 to 1 part by mass or about 0.02 to 0.5 part by mass with respect to 100 parts by mass of the monomer.

[0108] In addition, when a (meth)acrylic polymer having the above weight average molecular weight is produced using, for example, 2,2'-azobisisobutyronitrile as a polymerization initiator, the amount of the polymerization initiator used may be, for example, about 0.06 to 0.2 parts by mass or about 0.08 to 0.175 parts by mass relative to 100 parts by mass of the total amount of the monomer components.

[0109] Examples of the chain transfer agent include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol. The chain transfer agent may be used alone or in combination of two or more. The total content of the chain transfer agent is, for example, about 0.1 parts by mass or less relative to 100 parts by mass of the total amount of the monomer components.

[0110] Examples of emulsifiers used in emulsion polymerization include anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, polyoxyethylene alkyl ether ammonium sulfate, and sodium polyoxyethylene alkyl phenyl ether sulfate, and nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene fatty acid ester, and polyoxyethylene-polyoxypropylene block polymer. These emulsifiers may be used alone or in combination of two or more.

[0111] Furthermore, as reactive emulsifiers, emulsifiers having radical polymerizable functional groups such as propenyl groups and allyl ether groups are specifically exemplified by Aqualon HS-10, HS-20, KH-10, BC-05, BC-10, and BC-20 (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and Adeka Reasoap SE10N (manufactured by Asahi Denka Kogyo Co., Ltd.). Reactive emulsifiers are preferred because they are incorporated into the polymer chain after polymerization, improving water resistance. The amount of emulsifier used is 0.3 to 5 parts by mass, and more preferably 0.5 to 1 part by mass, based on 100 parts by mass of the total amount of monomer components, in terms of polymerization stability and mechanical stability.

[0112] The content of the (meth)acrylic polymer in the adhesive coating liquid is not particularly limited, and may be, for example, 3 mass % or more, or 5 mass % or more, and may be, for example, 30 mass % or less, 20 mass % or less, or 10 mass % or less, relative to the total mass of the adhesive coating liquid.

[0113] The adhesive coating liquid may or may not contain a monomer having one or two reactive double bonds in one molecule. The monomer having one or two reactive double bonds in one molecule is not particularly limited, but from the viewpoint of the reaction rate of the graft reaction, acrylic monomers, vinyl monomers, methacrylic monomers, and allyl monomers are preferred, and acrylic monomers are more preferred. The acrylic monomer is not particularly limited, but may be, for example, the same as the monomer exemplified as the monomer component of the acrylic polymer. In the monomer having one or two reactive double bonds in one molecule, the structure of the side chain is not particularly limited, but a heterocycle-containing monomer is preferred from the viewpoint of simultaneously achieving a high elastic modulus and a reduction in the amount of semi-high molecular weight polymer within an appropriate range.

[0114] In the case where the adhesive coating liquid contains a monomer having one or two reactive double bonds in one molecule, the content thereof is not particularly limited, and may be, for example, 0.1 mass % or more, 0.5 mass % or more, or 1 mass % or more, and may be, for example, 30 mass % or less, 20 mass % or less, or 10 mass % or less, relative to the total mass of the (meth)acrylic polymer in the adhesive coating liquid.

[0115] The laminate of the present disclosure can improve the durability of the adhesive layer formed from the adhesive coating liquid by including a monomer-type silane coupling agent in the adhesive coating liquid, and can maintain high durability even after being left for a long period of time, particularly in a humidified environment. Here, in the present disclosure, the adhesive coating liquid may be, for example, an adhesive (adhesive composition). The adhesive layer may be, for example, an adhesive layer formed from an adhesive (adhesive composition). The monomer type refers to a monomer, and in the present disclosure, the molecular weight of the monomer-type silane coupling agent may be, for example, 50 or more, 70 or more, 100 or more, or 150 or more, and may be, for example, 5000 or less, 3000 or less, 2000 or less, or 1000 or less.

[0116] In the present disclosure, since the adhesive layer contains a monomeric silane coupling agent, the initial refractive index of the void layer can be made lower than when, for example, an oligomeric silane coupling agent is used instead of the monomeric silane coupling agent.

[0117] The monomeric silane coupling agent may be, for example, a silane coupling agent having two or more alkoxysilyl groups in the molecule. Specific examples of the monomeric silane coupling agent having two or more alkoxysilyl groups in the molecule include amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane, (meth)acrylic group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane, and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane. These coupling agents are difficult to volatilize, and since they have multiple alkoxysilyl groups, they are effective in improving durability, and are therefore preferable. Examples of such coupling agents include KBM-802, KBM-303, and KBE-9007, both of which are trade names of Shin-Etsu Chemical Co., Ltd.

[0118] The number of alkoxysilyl groups in the monomeric silane coupling agent is not particularly limited, but is preferably 2 or more in the molecule. The amount of alkoxy groups in the monomeric silane coupling agent is preferably, for example, 10 to 60 mass%, more preferably 20 to 50 mass%, and even more preferably 20 to 40 mass% in the silane coupling agent. The type of alkoxy group is not limited, but examples include alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, propoxy, butoxy, pentyloxy, and hexyloxy. Among these, methoxy and ethoxy are preferred, and methoxy is more preferred. It is also preferred to include both methoxy and ethoxy in one molecule.

[0119] The monomeric silane coupling agent may contain, for example, an epoxy group. Also, the monomeric silane coupling agent may contain, for example, an acid anhydride group.

[0120] The monomeric silane coupling agent may be used alone or in a mixture of two or more. The total content of the monomeric silane coupling agent is 5.0 parts by mass or less, as described above, relative to 100 parts by mass of the (meth)acrylic polymer, but may be, for example, 4.0 parts by mass or less, 3.0 parts by mass or less, 2.0 parts by mass or less, or 1.0 parts by mass or less, and may be, for example, 0.01 parts by mass or more, 0.02 parts by mass or more, 0.03 parts by mass or more, 0.05 parts by mass or more, or 0.1 parts by mass or more. By setting the content within the above range, the increase in the initial refractive index can be suppressed, and further, the change in the refractive index after the heat durability test can be reduced.

[0121] The fact that the adhesive layer of the laminate of the present disclosure contains a silane coupling agent can be confirmed, for example, by TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry). Specifically, by measuring the adhesive layer of the laminate of the present disclosure by TOF-SIMS, it can be confirmed whether the adhesive layer contains a specific functional group (e.g., trimethoxysiloxy group, triethoxysiloxy group, dimethoxymethylsilyl group, etc.), and therefore it can be confirmed whether the adhesive layer contains a silane coupling agent. The TOF-SIMS measurement can be confirmed, for example, by the following measurement conditions.

[0122] [Sample preparation and measurement method] The adhesive layer of the laminate of the present disclosure is attached to a substrate made of an ITO (indium tin oxide) vapor-deposited glass plate, and the adhesive layer is peeled off from the substrate after autoclaving (50° C., 5 atm×15 min). The substrate surface after peeling is subjected to TOF-SIMS measurement. [Apparatus and measurement conditions] TOF SIMS device: ION TO TOF SIMS5 (product name of Hitachi High-Tech Corporation) Primary ions irradiated: Bi 3 2+ Primary ion acceleration voltage: 25 kV Measurement area: 200μm square *A neutralizing gun for charge compensation is used for measuring non-alkali glass.

[0123] In addition, the pressure-sensitive adhesive coating liquid (e.g., pressure-sensitive adhesive composition) used in the present disclosure may contain a silane coupling agent other than the monomer-type silane coupling agent. Examples of the silane coupling agent other than the monomer-type silane coupling agent include an oligomer-type silane coupling agent.

[0124] The weight average molecular weight (Mw) of the oligomer type silane coupling agent may be, for example, 300 or more. The laminate of the present invention can improve the durability of the adhesive layer formed from the adhesive coating liquid by including an oligomer type silane coupling agent in the adhesive coating liquid, and can maintain high durability even after being left for a long period of time, particularly excellent in durability under a humidified environment. Here, in the present invention, the adhesive coating liquid may be, for example, a pressure-sensitive adhesive (adhesive composition). The adhesive layer may be, for example, a pressure-sensitive adhesive layer formed from a pressure-sensitive adhesive (adhesive composition). Here, the term "oligomer type" refers to a polymer of a monomer having a dimer (polymerization degree of 2) or more and less than 100-mer (polymerization degree), and the weight average molecular weight of the oligomer type silane coupling agent is preferably about 300 to 30,000. In addition, in the present invention, the polymerization degree of the oligomer type silane coupling agent is not particularly limited.

[0125] The oligomer type silane coupling agent may be, for example, a silane coupling agent having two or more alkoxysilyl groups in the molecule.Specific examples include X-41-1053, X-41-1059A, and X-41-1056 manufactured by Shin-Etsu Chemical Co., Ltd. These coupling agents are preferred because they are difficult to volatilize and have multiple alkoxysilyl groups, which makes them effective in improving durability.

[0126] The number of alkoxysilyl groups in the oligomer-type silane coupling agent is not particularly limited, but is preferably 2 or more in the molecule. The amount of alkoxy groups in the oligomer-type silane coupling agent is, for example, preferably 10 to 60 mass%, more preferably 20 to 50 mass%, and even more preferably 20 to 40 mass% in the silane coupling agent. The type of alkoxy group is not limited, but examples include alkoxy groups having 1 to 6 carbon atoms such as methoxy, ethoxy, propoxy, butoxy, pentyloxy, and hexyloxy. Among these, methoxy and ethoxy are preferred, and methoxy is more preferred. It is also preferred to include both methoxy and ethoxy in one molecule.

[0127] As mentioned above, the oligomer type silane coupling agent may contain epoxy group.The epoxy equivalent of the oligomer type silane coupling agent is preferably 1000g / mol or less, more preferably 500g / mol or less, and more preferably 300g / mol or less.The lower limit of the epoxy equivalent is not particularly limited, but is preferably 200g / mol or more.

[0128] The oligomer type silane coupling agent preferably contains epoxy group, but may contain acid anhydride group.By using the oligomer type silane coupling agent containing acid anhydride group, the change in refractive index after the heat durability test can be reduced compared with the case where no silane coupling agent is used, and the adhesive strength between the adhesive layer and the low refractive index layer after the heat durability test can be improved.

[0129] The oligomeric silane coupling agent may be used alone or in a mixture of two or more. The total content of the oligomeric silane coupling agent may be, for example, 1 part by mass or less, and preferably, for example, 0.2 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic polymer. By setting the content within the above range, the increase in the initial refractive index can be suppressed, and further, the change in the refractive index after the heat durability test can be reduced.

[0130] Silane coupling agents other than the monomer-type silane coupling agents can be added within a range that does not impair the effects of the present disclosure, and the amount added is not particularly limited.

[0131] The adhesive coating liquid may contain a crosslinking agent, for example, as described above. The crosslinking agent is not particularly limited, but examples thereof include isocyanate-based crosslinking agents and epoxy-based crosslinking agents. The isocyanate-based crosslinking agent is not particularly limited, but examples thereof include aromatic isocyanates such as tolylene diisocyanate and xylylene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate, and aliphatic isocyanates such as hexamethylene diisocyanate. The epoxy crosslinking agent is not particularly limited, but examples thereof include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3′-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N′,N′-tetraglycidyl-m-xylylenediamine.

[0132] More specifically, the isocyanate-based crosslinking agent may be, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate, alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate, aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl isocyanate, trimethylolpropane / tolylene diisocyanate trimer adduct (Japan Examples of such polyisocyanates include isocyanate adducts such as a trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name: Coronate L), a trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name: Coronate HL), and an isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name: Coronate HX); polyether polyisocyanates, polyester polyisocyanates, and adducts of these with various polyols; and polyisocyanates which have been multifunctionalized with an isocyanurate bond, a biuret bond, an allophanate bond, or the like.

[0133] More specifically, examples of the epoxy crosslinking agent include "Tetrad C" manufactured by Mitsubishi Gas Chemical Company, Inc., "Tetrad X" manufactured by Mitsubishi Gas Chemical Company, Inc., and "S-610" manufactured by Synasia.

[0134] The crosslinking agent (e.g., isocyanate-based crosslinking agent, epoxy-based crosslinking agent) may be used alone or in a mixture of two or more kinds, and the total content may be, for example, 0.02 to 2 parts by mass, 0.04 to 1.5 parts by mass, or 0.05 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic polymer. The content of the isocyanate-based crosslinking agent is preferably 0.02 parts by mass or more from the viewpoint of cohesive strength, while it is preferably 2 parts by mass or less from the viewpoint of suppressing or preventing a decrease in adhesive strength due to excessive crosslinking. The content of the epoxy-based crosslinking agent is preferably 0.01 parts by mass or more from the viewpoint of void residual rate, while it is preferably 0.5 parts by mass or less from the viewpoint of peeling durability.

[0135] In the adhesive coating liquid, the crosslinking agent may be, for example, only an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent, or may or may not contain other crosslinking agents other than the isocyanate-based crosslinking agent or the epoxy-based crosslinking agent. Examples of the other crosslinking agents include organic crosslinking agents and polyfunctional metal chelates. Examples of the organic crosslinking agents include epoxy crosslinking agents and imine crosslinking agents. Examples of the organic crosslinking agents are isocyanate crosslinking agents and epoxy crosslinking agents. The polyfunctional metal chelate is a compound in which a polyvalent metal atom is covalently bonded or coordinately bonded to an organic compound. Examples of the polyvalent metal atom include Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. An example of the atom in the organic compound that forms a covalent bond or a coordinate bond is an oxygen atom, and examples of the organic compound include alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, and ketone compounds.

[0136] The adhesive coating liquid may or may not contain an organic peroxide. The organic peroxide is not particularly limited, but examples thereof include di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, and t-butyl hydroperoxide. Only one type may be used, or multiple types may be used in combination.

[0137] In a case where the adhesive coating liquid contains the organic peroxide, the content thereof is not particularly limited, and may be, for example, 0.02 mass % or more, 0.1 mass % or more, 0.5 mass % or more, 1 mass % or more, or 2.5 mass % or more relative to the total mass of the (meth)acrylic polymer in the adhesive coating liquid, and may be, for example, 20 mass % or less, 10 mass % or less, 8 mass % or less, or 6 mass % or less.

[0138] The pressure-sensitive adhesive coating liquid may further contain a solvent, etc. The solvent is not particularly limited, but for example, the polymerization solvent used in the solution polymerization in the production of the (meth)acrylic polymer may be used as it is.

[0139] Furthermore, the adhesive coating liquid may contain, as necessary, tackifiers, plasticizers, fillers made of glass fibers, glass beads, metal powders, other inorganic powders, pigments, colorants, fillers, antioxidants, ultraviolet absorbers, silane coupling agents, etc., and various additives may also be appropriately used within the scope of the object of the present disclosure. Also, the adhesive layer (adhesive layer) may contain fine particles and exhibit light diffusibility.

[0140] The adhesive layer in the laminate of the present disclosure can be formed by using the adhesive coating liquid, for example, by a method described later. The adhesive layer may have a weight average molecular weight of 30,000 to 600,000 in a molecular weight measurement of the adhesive layer by gel permeation chromatography. In addition, the content of low molecular weight components having a molecular weight of 10,000 or less in the sol component of the adhesive layer may be 20% by weight (mass%) or less in a molecular weight measurement of the adhesive layer by gel permeation chromatography. By setting the weight average molecular weight of the sol component or the content of low molecular weight components having a molecular weight of 10,000 or less in the sol component to the specific range, the adhesive is further less likely to penetrate into the voids of the void layer. The weight average molecular weight of the sol component may be, for example, 50,000 or more, for example, 550,000 or less or 500,000 or less, for example, 50 to 550,000 or 60 to 500,000. The content (ratio) of the component having a molecular weight of 10,000 or less in the sol content may be, for example, 20% by mass or less, as described above, and may be, for example, 15% by mass or less or 10% by mass or less, relative to the total amount of the sol content (100% by mass). The lower limit of the content (ratio) of the component having a molecular weight of 10,000 or less in the sol content is not particularly limited, and may be, for example, 0% by mass or more or a value exceeding 0% by mass, and may be, for example, 3% by mass or more. The content (ratio) of the component having a molecular weight of 10,000 or less in the sol content may be, for example, 3 to 15% by mass or 3 to 10% by mass.

[0141] [4. Manufacturing method of laminate] The method for producing the laminate of the present disclosure is not particularly limited, but can be performed, for example, by the production method described below. However, the following description is an example and does not limit the present disclosure in any way. The void layer of the present disclosure is not particularly limited, but is, for example, as described above. In addition, the method for producing the void layer of the present disclosure is also not particularly limited, as described above, and can be produced, for example, by the method described in WO 2019 / 065999 and WO 2019 / 065803.

[0142] The manufacturing method of the laminate of the present disclosure may include, for example, a tacky adhesive layer manufacturing step of manufacturing the tacky adhesive layer, and a lamination step of laminating the tacky adhesive layer to the void layer. The manufacturing method of the tacky adhesive layer may include, for example, a tacky adhesive coating liquid application step of applying the tacky adhesive coating liquid to a substrate, and a heat drying step of heating and drying the substrate to which the tacky adhesive coating liquid has been applied. For example, the tacky adhesive layer may be formed on the void layer of the present disclosure by laminating the tacky adhesive layer side of an adhesive tape or the like having the tacky adhesive layer of the present disclosure laminated on a substrate onto the void layer of the present disclosure. In this case, the substrate such as the adhesive tape may be left as it is or may be peeled off from the tacky adhesive layer. In particular, by peeling off the substrate to form a void layer-containing tacky adhesive sheet that does not have a substrate (substrate-less), the thickness can be significantly reduced, and an increase in the thickness of a device or the like can be suppressed. In the present disclosure, the "adhesive" and the "adhesive layer" refer to, for example, an agent or layer that is intended to be peeled off from an adherend. In the present disclosure, the terms "adhesive" and "adhesive layer" refer to, for example, an agent or layer that is not intended to be removably attached to an adherend. However, in the present disclosure, the terms "adhesive" and "adhesive" are not necessarily clearly distinguishable from each other, and the terms "adhesive layer" and "adhesive layer" are not necessarily clearly distinguishable from each other. In the present disclosure, the adhesive layer can be produced, for example, by using the adhesive coating liquid as described above.

[0143] The adhesive layer manufacturing step can be carried out, for example, as follows. First, the adhesive coating liquid is manufactured by a mixing step of mixing all the components of the adhesive coating liquid. The adhesive coating liquid may contain, for example, the (meth)acrylic polymer as described above, and may further contain, for example, a crosslinking agent (for example, an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent). The adhesive coating liquid may contain, for example, the (meth)acrylic polymer, a monomer having one or two reactive double bonds in one molecule, and an organic peroxide. At this time, when the adhesive coating liquid contains other components, the other components may also be mixed together. For example, the polymerization solvent used in the production of the (meth)acrylic polymer may be mixed as it is as a component of the adhesive coating liquid without removing it. In addition, the manufacturing method of the adhesive coating liquid may include, but may not include, other steps other than the mixing step, and may simply mix all the components of the adhesive coating liquid in the mixing step.

[0144] Next, the adhesive coating liquid is applied to a substrate (adhesive coating liquid application step). The substrate is not particularly limited, and may be, for example, a substrate such as a film. The substrate may be, for example, a substrate made of a thermoplastic resin, a substrate made of glass, an inorganic substrate such as silicon, a plastic formed from a thermosetting resin, an element such as a semiconductor, or a carbon fiber-based material such as a carbon nanotube, but is not limited thereto. The substrate may be, for example, a film or a plate. The thermoplastic resin may be, for example, polyethylene terephthalate (PET), acrylic, cellulose acetate propionate (CAP), cycloolefin polymer (COP), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), or the like. In the adhesive coating liquid application step, the thickness of the adhesive coating liquid is not particularly limited, and may be appropriately adjusted so that the thickness of the adhesive layer after drying is a predetermined thickness. The thickness of the adhesive layer after drying is also not particularly limited, and may be, for example, as described below.

[0145] Next, the substrate coated with the adhesive coating liquid is heated and dried (heat drying step). In this heat drying step, the temperature of the heat drying is not particularly limited, but may be, for example, 50°C or more, 80°C or more, 100°C or more, or 155°C or more, and may be, for example, 200°C or less, 180°C or less, or 160°C or less. The time of the heat drying is not particularly limited, but may be, for example, 0.5 minutes or more, 1 minute or more, or 3 minutes or more, and may be, for example, 60 minutes or less, 30 minutes or less, 20 minutes or less, or 10 minutes or less. In this heat drying step, for example, a crosslinking reaction and graft polymerization occur between the (meth)acrylic polymer and the crosslinking agent. As a result, for example, as described above, the amount of the semi-high molecular weight polymer present in the adhesive coating liquid is reduced, and the adhesive layer becomes less likely to penetrate into the voids of the void layer. In this manner, the adhesive layer used in the laminate of the present disclosure can be manufactured.

[0146] Next, the adhesive layer is bonded to the void layer (bonding step). This method is not particularly limited, but for example, as described above, the adhesive layer side of an adhesive tape or the like in which the adhesive layer of the present disclosure is laminated on a substrate may be bonded to the void layer of the present disclosure to form the adhesive layer on the void layer of the present disclosure. In this manner, the laminate of the present disclosure can be manufactured.

[0147] In the manufacturing method of the laminate of the present disclosure, for example, a heating step of heating the adhesive layer and the void layer may be performed after the lamination step. Hereinafter, this heating step may be referred to as an "aging step". In the heating step (aging step), the heating temperature is not particularly limited, but may be, for example, 40°C or more, 45°C or more, or 50°C or more, and may be, for example, 80°C or less, 70°C or less, 60°C or less, or 55°C or less. The heating time is not particularly limited, but may be, for example, 1 minute or more, 10 minutes or more, 60 minutes or more, or 1800 minutes or more, and may be, for example, 3000 minutes or less, 2800 minutes or less, 2500 minutes or less, or 2000 minutes or less. In this aging step, for example, the intermediate layer is formed by the union of the void layer and the adhesive layer. Then, for example, as described above, the intermediate layer serves as a stopper, and the decrease in porosity caused by the voids in the void layer being filled with the adhesive can be suppressed. In addition, the integration of the void layer and the adhesive layer may be such that the adhesive layer is embedded in the voids of the void layer and chemically bonded thereto, or the adhesive layer is embedded in the voids of the void layer.

[0148] The adhesive layer can protect the void layer from physical damage (particularly scratches). The adhesive layer is preferably excellent in pressure resistance so that the void layer is not crushed even in a void layer-containing adhesive sheet that does not have a substrate (substrate-less), but is not particularly limited. The thickness of the adhesive layer is not particularly limited, but is, for example, 0.1 to 100 μm, 5 to 50 μm, 10 to 30 μm, or 12 to 25 μm.

[0149] The laminate of the present disclosure thus obtained may be further laminated with another film (layer) as described above to form a laminate structure including the void layer (porous structure). In this case, in the laminate structure, each component may be laminated via, for example, the adhesive layer (adhesive or adhesive).

[0150] The lamination of each of the components may be performed, for example, by continuous processing (so-called roll to roll, etc.) using a long film, since this is efficient. When the substrate is a molded product, element, etc., the components may be laminated after batch processing.

[0151] The method of forming the laminate of the present disclosure on a substrate (resin film) will be described below with reference to the continuous processing steps, taking the laminate 10d of Fig. 3(a) as an example. Note that the film-forming method described below is merely an example, and is not limited thereto.

[0152] The substrate may be the resin film described above. In this case, the void layer of the present disclosure is obtained by forming the void layer on the substrate. The void layer of the present disclosure can also be obtained by laminating the void layer on the resin film described above in the description of the void layer of the present disclosure after forming the void layer on the substrate.

[0153] The method for producing the laminate 10d in Fig. 3(a) includes, for example, first forming a void layer 11 on a substrate 14, further forming a tacky adhesive layer 12 on the void layer 11, and further forming an intermediate layer 13 by combining the void layer 11 and the tacky adhesive layer 12. More specifically, this production method includes, for example, a coating step (1) of coating a sol particle liquid of a pulverized product of a gel-like compound on a substrate (resin film) 14 to form a coating film, a drying step (2) of drying the sol particle liquid to form a coating film after drying, a chemical treatment step (e.g., a crosslinking step) (3) of chemically treating the coating film (e.g., a crosslinking treatment) to form the void layer 11, a bonding step (4) of bonding the tacky adhesive layer 12 on the void layer 11, and an intermediate layer formation step (5) of reacting the void layer 11 with the tacky adhesive layer 12 to form the intermediate layer 13. The method for producing the sol particle liquid of the pulverized product of the gel-like compound is not particularly limited. Specifically, the sol particle liquid can be produced by the method described in, for example, International Publication No. 2019 / 065999 or International Publication No. 2019 / 065803. The sol particle liquid can also be produced by the method described in, for example, "Reference Example 1" of the Examples of the present application described later. Although not shown, the method for producing a laminate of the present disclosure further includes a tacky adhesive layer production step of producing the tacky adhesive layer by the tacky adhesive layer production method of the present disclosure, as described above, and a lamination step of laminating the tacky adhesive layer to the void layer. The method for producing a tacky adhesive layer of the present disclosure further includes a tacky adhesive coating liquid application step of applying the tacky adhesive coating liquid to a substrate, and a heat drying step of heating and drying the substrate to which the tacky adhesive coating liquid has been applied. The chemical treatment step (crosslinking step) (3) corresponds to the "void layer formation step" of forming a void layer in the laminate of the present disclosure. The intermediate layer formation step (5) corresponds to the heating step (aging step) described above. The intermediate layer forming step (5) (hereinafter sometimes referred to as the "aging step") may also serve as, for example, a step of improving the strength of the void layer 11 (a cross-linking reaction step of causing a cross-linking reaction inside the void layer 11), in which case the void layer 11 changes to a void layer 11 with further improved strength after the intermediate layer forming step (5). However, the present disclosure is not limited thereto, and for example, the void layer 11 does not need to change after the intermediate layer forming step (5).Also, the laminating step (4) may be laminating an adhesive tape having a tacky adhesive layer on a substrate as described above. In FIG. 3(a), the substrate 14 on which the tacky adhesive coating liquid is applied (the tacky adhesive layer 12 is formed) may be, for example, peeled off and removed from the tacky adhesive layer 12, or may be left on the tacky adhesive layer 12 as it is. By the above steps (1) to (5), as shown in FIG. 3(a), a laminated film (laminate) can be manufactured in which the void layer 11, the intermediate layer 13, and the tacky adhesive layer 12 are laminated in the above order on the resin film 14. However, the intermediate layer forming step (5) may not be performed, and the laminate of the present disclosure manufactured may not include an intermediate layer. Furthermore, the manufacturing method of the laminate of the present disclosure may or may not include steps other than those described above as appropriate. Also, for example, as in the laminated film (laminate) 10d of FIG. 3(a), another sheet 14 may be laminated on the tacky adhesive layer 12. Furthermore, while the laminated film (laminate) 10d in Figure 3(a) has an adhesive layer 12 provided on only one side of the air gap layer 11, the adhesive layer 12 may be provided on both sides of the air gap layer 11, for example, as in the laminate 10e in Figure 3(b).

[0154] In the coating step (1), the coating method of the sol particle liquid is not particularly limited, and a general coating method can be adopted. Examples of the coating method include a slot die method, a reverse gravure coating method, a microgravure method (microgravure coating method), a dip method (dip coating method), a spin coating method, a brush coating method, a roll coating method, a flexographic printing method, a wire bar coating method, a spray coating method, an extrusion coating method, a curtain coating method, and a reverse coating method. Among these, from the viewpoint of productivity, smoothness of the coating film, and the like, an extrusion coating method, a curtain coating method, a roll coating method, a microgravure coating method, and the like are preferable. The coating amount of the sol particle liquid is not particularly limited, and can be appropriately set, for example, so that the thickness of the void layer 11 is appropriate. The thickness of the void layer 11 is not particularly limited, and is, for example, as described above.

[0155] In the drying step (2), the sol particle liquid is dried (i.e., the dispersion medium contained in the sol particle liquid is removed) to form the dried coating film (precursor of the void layer). The conditions for the drying process are not particularly limited and are as described above.

[0156] Furthermore, in the chemical treatment step (3), the dried coating film containing the catalyst or catalyst generator (e.g., a photoactive catalyst, a photocatalyst generator, a thermally active catalyst, or a thermal catalyst generator) added before coating is irradiated with light or heated to chemically bond (e.g., crosslink) the pulverized materials in the dried coating film to each other, thereby forming a void layer 11. The light irradiation or heating conditions in the chemical treatment step (3) are not particularly limited and are as described above.

[0157] On the other hand, although not shown, the adhesive layer of the present disclosure is separately manufactured by the adhesive layer manufacturing step. The adhesive layer manufacturing step (the adhesive layer manufacturing method of the present disclosure) is, for example, as described above.

[0158] Further, a bonding step (4) and an intermediate layer forming step (5) are performed. As described above, the intermediate layer forming step (5) is a heating step in which the adhesive layer 12 and the void layer 11 are heated after the bonding step (4). For example, when the adhesive is an adhesive composition containing a polymer (e.g., a (meth)acrylic polymer) and a crosslinking agent, the polymer may be crosslinked by the crosslinking agent by the heating step. For example, the heating step may also serve as a step of drying the adhesive. Also, for example, the heating step may also serve as the intermediate layer forming step (5). The temperature of the heating step is not particularly limited, but is, for example, 70 to 160°C, 80 to 155°C, or 90 to 150°C. The time of the heating step is not particularly limited, but is, for example, 1 to 10 minutes, 1 to 7 minutes, or 2 to 5 minutes. EXAMPLES

[0159] Next, examples of the present disclosure will be described, but the present disclosure is not limited to the following examples.

[0160] In the following Reference Examples, Examples, and Comparative Examples, the number of parts (relative amount used) of each substance is in parts by mass (parts by weight) unless otherwise specified. In the following Reference Examples, Examples, and Comparative Examples, a pressure-sensitive adhesive (pressure-sensitive adhesive composition) described below was used as the pressure-sensitive adhesive. In the following Reference Examples, Examples, and Comparative Examples, the term "pressure-sensitive adhesive layer" corresponds to the "pressure-sensitive adhesive layer". That is, in the following Reference Examples, Examples, and Comparative Examples, the terms "pressure-sensitive adhesive layer" and "pressure-sensitive adhesive layer" are synonymous unless otherwise specified.

[0161] In the following Reference Examples, Examples and Comparative Examples, the weight average molecular weight (Mw) of the (meth)acrylic polymer, the gel fraction of the adhesive layer, the thickness of each layer and the refractive index were measured by the following measurement methods.

[0162] <Method for measuring molecular weight of (meth)acrylic polymer> The weight-average molecular weight (Mw) of the (meth)acrylic polymer was calculated from the molecular weight distribution curve measured by gel permeation chromatography (GPC). ·Analyzer:Waters,Alliance Column: Tosoh Corporation, G7000HXL+GMHXL+GMHXL Column size: 7.8mmφ×30cm each, total 90cm Column temperature: 40℃ ·Flow rate: 0.8mL / min ·Injection volume: 100μL ·Eluent: THF (acid added) Detector: Differential refractometer (RI) Standard sample: polystyrene

[0163] <Method for measuring gel fraction of adhesive layer> Approximately 0.1 g was scraped off from the optical adhesive layer formed on the release-treated surface of the separator film within 1 minute of preparation, and this was used as sample 1. The sample 1 was wrapped in a Teflon (registered trademark) film (trade name "NTF1122", manufactured by Nitto Denko Corporation) having a diameter of 0.2 μm, and then tied with a kite string, and this was used as sample 2. The weight of sample 2 before being subjected to the following test was measured, and this was used as weight A. The weight A is the total weight of sample 1 (adhesive layer), the Teflon (registered trademark) film, and the kite string. The total weight of the Teflon (registered trademark) film and the kite string was used as weight B. Next, the sample 2 was placed in a 50 ml container filled with ethyl acetate and left to stand at 23° C. for one week. Thereafter, the sample 2 was taken out of the container, dried in a dryer at 130° C. for 2 hours to remove the ethyl acetate, and the weight of the sample 2 was measured. The weight of the sample 2 after being subjected to the above test was measured, and this was used as weight C. The gel fraction was then calculated from the following formula: Gel fraction (mass%) = (CB) / (AB) x 100

[0164] <How to measure thickness> The thickness of the adhesive layer was determined by measuring the thickness at five points on the adhesive layer using a dial gauge and taking the average value. The thickness of the intermediate layer was determined by taking the thickness of the intermediate layer, which is a part of the adhesive layer with a different contrast between the adhesive layer and the low refractive index layer in the SEM image, as the average value of the thickness measured at two points on the SEM image.

[0165] <Method of measuring refractive index> The refractive index was measured by the above-mentioned refractive index evaluation method.

[0166] In the adhesive layers in the following Reference Examples, Examples, and Comparative Examples, it is assumed that the polymer (acrylic polymer) is crosslinked by the crosslinking agent through heating and drying the applied adhesive, thereby forming a crosslinked structure, but the crosslinked structure has not been confirmed.

[0167] [Reference Example 1: Production of coating solution for forming void layer] First, a gel having a porous structure (a silicone porous body) was produced by gelling the silicon compound (step (1) below) and aging (step (2) below). After that, the following steps (3) morphology control step, (4) solvent replacement step, and (5) gel crushing step were performed to obtain a coating liquid for forming a void layer (liquid containing gel crushed material). In this reference example, the following step (3) morphology control step was performed as a separate step from the following step (1) as described below. However, the present disclosure is not limited to this, and for example, the following step (3) morphology control step may be performed during the following step (1).

[0168] (1) Gelation of silicon compounds 9.5 kg of MTMS, a precursor of a silicon compound, was dissolved in 22 kg of DMSO. 5 kg of 0.01 mol / L oxalic acid solution was added to the mixture, and the mixture was stirred at room temperature for 120 minutes to hydrolyze MTMS and generate tris(hydroxy)methylsilane.

[0169] 3.8 kg of 28% ammonia water and 2 kg of pure water were added to 55 kg of DMSO, and the hydrolyzed mixture was then added and stirred at room temperature for 60 minutes. The liquid after stirring for 60 minutes was poured into a stainless steel container measuring 30 cm in length, 30 cm in width, and 5 cm in height and allowed to stand at room temperature to gel tris(hydroxy)methylsilane and obtain a gel-like silicon compound.

[0170] (2) Aging process The gel-like silicon compound obtained by the gelation treatment was incubated at 40°C for 20 hours to perform aging treatment, and the rectangular solid-shaped lump gel was obtained. Since the amount of DMSO (a high-boiling point solvent with a boiling point of 130°C or higher) used in the raw material was about 83% by mass of the entire raw material, it was clear that this gel contained 50% by mass or more of a high-boiling point solvent with a boiling point of 130°C or higher. Furthermore, since the amount of MTMS (a monomer that is a constituent unit of the gel) used in the raw material was about 8% by mass of the entire raw material, it was clear that the content of a solvent (methanol in this case) with a boiling point of less than 130°C generated by hydrolysis of the monomer (MTMS) that is a constituent unit of the gel was 20% by mass or less.

[0171] (3) Morphology control process Water, which was a replacement solvent, was poured onto the gel synthesized in the 30 cm × 30 cm × 5 cm stainless steel vessel by the steps (1) and (2). Next, the cutting blade of a cutting tool was slowly inserted into the gel from above in the stainless steel vessel, and the gel was cut into a rectangular parallelepiped with a size of 1.5 cm × 2 cm × 5 cm.

[0172] (4) Solvent replacement process Next, a solvent substitution step was carried out as follows (4-1) to (4-3).

[0173] (4-1) After the "(3) morphology control step", the gel-like silicon compound was immersed in water of 8 times the weight of the gel-like silicon compound, and slowly stirred for 1 hour so that only the water was circulating. After 1 hour, the water was replaced with the same amount of water, and further stirred for 3 hours. After that, the water was replaced again, and then heated at 60°C for 3 hours while slowly stirring.

[0174] (4-2) After (4-1), the water was replaced with isopropyl alcohol in an amount four times the weight of the gel silicon compound, and the mixture was heated at 60° C. for 6 hours while stirring.

[0175] (4-3) After (4-2), the isopropyl alcohol was replaced with the same weight of isobutyl alcohol, and the mixture was heated at 60° C. for 6 hours to replace the solvent contained in the gel-like silicon compound with isobutyl alcohol. In this manner, the gel for producing a gap layer according to the present disclosure was produced.

[0176] (5) Gel crushing process The gel (gel-like silicon compound) after the solvent replacement step (4) was subjected to two stages of pulverization: continuous emulsification dispersion (Milder MDN304, manufactured by Pacific Machinery Co., Ltd.) in the first pulverization stage, and high-pressure medialess pulverization (Starburst HJP-25005, manufactured by Sugino Machine Co., Ltd.). In this pulverization process, 26.6 kg of isobutyl alcohol was added to 43.4 kg of the gel containing the gel-like silicon compound subjected to solvent replacement, and then the first pulverization stage was pulverized for 20 minutes by circulation pulverization, and the second pulverization stage was pulverized at a pulverization pressure of 100 MPa. In this way, an isobutyl alcohol dispersion (containing gel pulverized product) in which nanometer-sized particles (pulverized product of the gel) are dispersed was obtained. Furthermore, 224 g of a 1.5% solution of WPBG-266 (trade name, manufactured by Wako) in methyl isobutyl ketone was added to 3 kg of the gel powder-containing liquid, and then 67.2 g of a 5% solution of bis(trimethoxysilyl)ethane (manufactured by TCI) in methyl isobutyl ketone was added, and then 31.8 g of N,N-dimethylformamide was added and mixed to obtain a coating liquid.

[0177] In the above manner, a coating liquid (containing pulverized gel) for forming a void layer of this reference example (reference example 1) was produced. The peak pore diameter of the pulverized gel (microporous particles) in the coating liquid (containing pulverized gel) for forming a void layer was measured by the above-mentioned method and was found to be 12 nm.

[0178] [Reference Example 2: Formation of adhesive layer] The adhesive layer of this reference example (Reference Example 2) was formed by the following procedures (1) and (2).

[0179] (1) Preparation of (meth)acrylic polymer (Preparation of (meth)acrylic polymer (A1)) A monomer mixture containing 79.5 parts of butyl acrylate, 15 parts of N-acryloylmorpholine, 5 parts of acrylic acid, and 0.5 parts of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 70 parts of ethyl acetate with respect to 100 parts of the monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 2 hours to prepare a solution of a (meth)acrylic polymer (A1) having a weight average molecular weight (Mw) of 3.4 million and Mw / Mn=2.5.

[0180] (Preparation of (meth)acrylic polymer (A2)) In (Preparation of (meth)acrylic polymer (A1)), the monomer composition was changed to 79.5 parts of butyl acrylate, 7.5 parts of N-acryloylmorpholine, 5 parts of acrylic acid, and 0.5 parts of 4-hydroxybutyl acrylate, and the polymerization reaction time was changed to 8 hours. The rest of the process was the same as in (Preparation of (meth)acrylic polymer (A1)), and a solution of (meth)acrylic polymer (A2) having a weight average molecular weight (Mw) of 2,900,000 and Mw / Mn=4.2 was prepared.

[0181] (2) (Preparation of Pressure-Sensitive Adhesive Composition) An acrylic pressure-sensitive adhesive composition was prepared by blending 0.5 parts of a monomeric silane coupling agent (trade name "KBM-802" manufactured by Shin-Etsu Chemical Co., Ltd.), 0.2 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.1 parts of an epoxy crosslinking agent (trade name "Tetrad C" manufactured by Mitsubishi Gas Chemical Co., Inc.), and 0.2 parts of benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Corporation) per 100 parts of the solid content of the (meth)acrylic polymer (A1) or (A2).

[0182] (3) (Formation of adhesive layer) Next, the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (separator film: MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) treated with a silicone-based release agent so that the adhesive layer would have a thickness of 10 μm after drying, and dried at 155° C. for 1 minute to form an adhesive layer (tacky adhesive layer) on the surface of the separator film.

[0183] [Example 1] (Manufacture of laminates) The high porosity layer-forming coating liquid prepared in Reference Example 1 was applied to an acrylic substrate and dried to form a void layer with a thickness of about 850 nm (void ratio: 59% by volume). Next, UV irradiation (300 mJ) was performed from the void layer surface. Thereafter, the adhesive layer (in this example, (meth)acrylic polymer (A1) was used) with a thickness of 10 μm obtained in Reference Example 2 was bonded to the void layer surface, and aging was performed at 60° C. for 20 hours to produce the laminate of this example.

[0184] [Examples 2 to 12 and Comparative Examples 1 to 2] The laminates of Examples 2 to 12 and Comparative Examples 1 and 2 were produced as follows.

[0185] For Examples 2 to 12 and Comparative Examples 1 to 2, the type of (meth)acrylic polymer was as shown in Table 1 below, the type and amount (parts by mass) of monomeric silane coupling agent was as shown in Table 1 below, and the amount (parts by mass) of crosslinking agent was as shown in Table 1 below. Except for this, the solution of the acrylic pressure-sensitive adhesive composition used in the production of the laminates of Examples 2 to 12 and Comparative Examples 1 to 2 was prepared in the same manner as in Example 1. Furthermore, the solution of the acrylic pressure-sensitive adhesive composition was used to prepare a pressure-sensitive adhesive layer in the same manner as in Example 1, to produce the laminates of Examples 2 to 12 and Comparative Examples 1 to 2. In Table 1 below, all of the monomeric silane coupling agents are manufactured by Shin-Etsu Chemical Co., Ltd., and the "type" of the monomeric silane coupling agent is the product name of Shin-Etsu Chemical Co., Ltd.

[0186] [Heat durability test] Furthermore, the laminates of the present embodiment and the comparative example manufactured as described above were placed in an oven at a temperature of 65° C. and a relative humidity of 95%, and a heat durability test was performed for 500 hours. From the refractive index before and after the heat durability test, the change in the refractive index was calculated using the above formula (1). These results are shown in Table 1.

[0187] The evaluation criteria for the initial refractive index in Table 1 are as follows: ◎: Less than 1.19 ○: 1.19 or more, less than 1.20 ×: 1.20 or higher

[0188] The evaluation criteria for the refractive index (amount of change) after the heat durability test in Table 1 are as follows: ◎: Less than 0.03 ○: 0.03 or more, less than 0.04 ×:0.04 or more

[0189] The evaluation criteria for the rate of change in refractive index after the heat durability test in Table 1 are as follows. The rate of change in refractive index (%) after the heat durability test in Tables 1 and 2 is (|nn 0 | / n 0 ) × 100. n 0 is the refractive index (initial refractive index) of the air gap layer before the heat durability test, as in the above formula (1), and n is the refractive index of the air gap layer after the heat durability test, as in the above formula (1). ◎: Less than 2.0% ○: 2.0% or more, less than 3.0% ×: 3.0% or more

[0190] The meanings of the terms shown in Table 1 are as follows: The numbers in Table 1 indicate the amount (parts by mass) of each component added. [(Meth)acrylic polymer] "A1" or "A2" indicates whether the adhesive layer formed was made of the (meth)acrylic polymer A1 or A2 described in Reference Example 2. The adhesive layer was formed in the same manner as in Reference Example 2. [Monomer-type silane coupling agents] Type: This indicates the type of monomeric silane coupling agent used in each Example and Comparative Example, and is the trade name of Shin-Etsu Chemical Co., Ltd., as described above. Functional group: indicates the type of functional group possessed by the monomeric silane coupling agent used in each Example and Comparative Example. Methoxy or ethoxy: indicates whether the monomeric silane coupling agent used in each Example and Comparative Example has a methoxy group or an ethoxy group, or whether it has a silanol group in the form of a hydrolysis of these groups. [Crosslinking agent] Isocyanate: Adduct of trimethylolpropane and tolylene diisocyanate (product name "Coronate L" manufactured by Tosoh Corporation) Epoxy: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "Tetrad C" manufactured by Mitsubishi Gas Chemical Company, Inc.) Peroxide: Benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Co., Ltd.)

[0191] [Table 1]

[0192] As shown in Table 1, in Examples 1 to 12 in which a monomer-type silane coupling agent was used and the amount of the silane coupling agent added was 5.0 parts by mass or less, the initial refractive index was low, the refractive index (change amount) after the heat durability test was also low, and the peel durability was also excellent. That is, in the laminates of Examples 1 to 12, the adhesive was unlikely to penetrate into the voids of the void layer, so the initial refractive index was low and the heat durability was excellent, and these effects were compatible with strong adhesion between the adhesive layer and the low refractive index layer. In contrast, when the amount of the monomer-type silane coupling agent added was more than 5.0 parts by mass (Comparative Example 1) or when the silane coupling agent was not used (Comparative Example 2), the adhesive was likely to penetrate into the voids of the void layer, so that the initial refractive index, heat durability, and adhesion between the adhesive layer and the low refractive index layer were all poor. More specifically, Comparative Example 1 had a poor initial refractive index, and Comparative Example 2 had a good initial refractive index but poor heat durability. In addition, in all of Examples 1 to 12 and Comparative Examples 1 and 2, a fluorine compound was not used when forming the void layer, so the void layer did not contain a fluorine compound. In addition, as shown in Table 1, the monomer-type silane coupling agents used in Examples 1 to 12 had a mercapto group, an epoxy group, an isocyanate group (isocyanato group), an amino group, an acrylic group, a styryl group, a vinyl group, an isocyanurate group, an acetoacetyl group, a silane group, or a carboxylic acid group (carboxy group) as a functional group, but any functional group could achieve the above-mentioned effect.

[0193] The present disclosure can be described, for example, as in the following supplementary notes. However, the supplementary notes are merely examples, and the present disclosure is not limited to these forms.

[0194] (Appendix 1) A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, the adhesive layer is formed of an adhesive containing a (meth)acrylic polymer and a monomer-type silane coupling agent, A laminate comprising the monomeric silane coupling agent in an amount of 5.0 parts by mass or less based on 100 parts by mass of the (meth)acrylic polymer. (Appendix 2) 2. The laminate according to claim 1, wherein the (meth)acrylic polymer has a weight average molecular weight (Mw) of 1.5 million to 4 million. (Appendix 3) the adhesive layer is formed from an adhesive containing the (meth)acrylic polymer and a crosslinking agent, 3. The laminate according to claim 1 or 2, wherein the pressure-sensitive adhesive has a gel fraction of more than 85%. (Appendix 4) 4. The laminate according to any one of claims 1 to 3, wherein the (meth)acrylic polymer contains, as monomer units, 1 to 30 mass % of a nitrogen-containing monomer. (Appendix 5) 5. The laminate according to claim 4, wherein the nitrogen-containing monomer is a heterocycle-containing acrylic monomer. (Appendix 6) 6. The laminate according to any one of claims 1 to 5, wherein the (meth)acrylic polymer contains 0.5 to 20% by mass of acrylic acid as a monomer unit. (Appendix 7) 7. The laminate according to any one of claims 1 to 6, wherein the air gap layer does not contain an organic fluorine compound. (Appendix 8) 8. The laminate according to any one of claims 1 to 7, wherein the change in refractive index of the air gap layer before and after a heat durability test in which the laminate is maintained at a temperature of 65°C and a relative humidity of 95% for 500 hours satisfies the following formula (1). |nn 0 |<0.04 (1) In the formula (1), n is the refractive index of the air gap layer after the heat durability test, n 0 is the refractive index of the air gap layer before the heat durability test. (Appendix 9) An intermediate layer is present between the void layer and the adhesive layer, 9. The laminate according to any one of claims 1 to 8, wherein the intermediate layer is a layer formed by combining the void layer and the adhesive layer. (Appendix 10) 10. The laminate according to claim 9, wherein the intermediate layer has a thickness of 10 to 100 nm. (Appendix 11) 11. An optical member comprising the laminate according to any one of claims 1 to 10. (Appendix 12) 12. An optical device comprising the optical member according to claim 11. [Industrial Applicability]

[0195] As described above, according to the present disclosure, it is possible to provide a laminate, an optical member, and an optical device that achieve both adhesion or bonding strength and the difficulty of the adhesive or adhesive penetrating into the gaps of the void layer. The use of the present disclosure is not particularly limited. For example, the optical device of the present disclosure is not particularly limited, and examples thereof include image display devices and lighting devices. Examples of the image display devices include liquid crystal displays, organic EL displays, micro LED displays, and the like. Examples of the lighting devices include organic EL lighting, and the like. According to the laminate of the present disclosure, for example, the adhesive or adhesive is unlikely to penetrate into the gaps of the void layer even under high temperature and high humidity, so that it is particularly suitable for use under high durability conditions such as in-vehicle use. Furthermore, the use of the laminate of the present disclosure is not limited to the optical member and optical device of the present disclosure, and is optional, and can be used for a wide range of applications. [Explanation of symbols]

[0196] 10, 10a, 10b, 10c, 10d, 10e Laminate 11 Porous layer 12 Adhesive layer 13. Middle Class 14 Base material

Claims

1. A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, the adhesive layer is formed of an adhesive containing a (meth)acrylic polymer and a monomer-type silane coupling agent, A laminate comprising the monomeric silane coupling agent in an amount of 5.0 parts by mass or less based on 100 parts by mass of the (meth)acrylic polymer.

2. 2. The laminate according to claim 1, wherein the (meth)acrylic polymer has a weight average molecular weight (Mw) of 1.5 million to 4 million.

3. the adhesive layer is formed from an adhesive containing the (meth)acrylic polymer and a crosslinking agent, The laminate according to claim 1 , wherein the pressure-sensitive adhesive has a gel fraction of more than 85%.

4. 2. The laminate according to claim 1, wherein the (meth)acrylic polymer contains, as monomer units, 1 to 30% by mass of a nitrogen-containing monomer.

5. 5. The laminate according to claim 4, wherein the nitrogen-containing monomer is a heterocycle-containing acrylic monomer.

6. 2. The laminate according to claim 1, wherein the (meth)acrylic polymer contains 0.5 to 20% by mass of acrylic acid as a monomer unit.

7. 2. The laminate according to claim 1, wherein the air gap layer does not contain an organic fluorine compound.

8. 2. The laminate according to claim 1, wherein a change in refractive index of the porous layer before and after a heat durability test in which the laminate is maintained at a temperature of 65° C. and a relative humidity of 95% for 500 hours satisfies the following formula (1). |n-n 0 |<0.04 (1) In the formula (1), n is the refractive index of the air gap layer after the heat durability test, n 0 is the refractive index of the air gap layer before the heat durability test.

9. An intermediate layer is present between the void layer and the adhesive layer, 2. The laminate according to claim 1, wherein the intermediate layer is a layer formed by combining the void layer and the adhesive layer.

10. 10. The laminate according to claim 9, wherein the intermediate layer has a thickness of 10 to 100 nm.

11. An optical member comprising the laminate according to claim 1 .

12. An optical device comprising the optical member according to claim 11.

Citation Information

Patent Citations

  • Surface light-emitting device and manufacture thereof

    JP1998062626A

  • Backlight panel, light guide plate, reflection plate, and adhesive sheet

    JP2012156082A

  • Laminate, polarizing plate, optical material, display device and touch panel

    JP2014046518A